Formação continuada no ensino superior: um estudo com professores que atuam em cursos de Educação Física - Temp, Haury (2013)
This study is inserted into the Line of Formation Search, Knowledge and Professional Development (PPGE/CE/UFSM) which has as main objective to identify the strategies for continuing education of Physical Education professionals who work in higher education. As specific objectives we will verify the conceptions that the Physical Education teachers who work in higher education has about the thematic, we will seek to recognize how the teachers (re)build their pedagogical action from their continuing education how the institutions encourage their teachers. The search characterized as qualitative descriptive; the six participants were selected according specific criteria as the interest to participate in the research, be graduated in Physical Education and work in the programs in Physical Education in one of two IES of Santa Maria. First was performed contact to the teachers, scheduling and routing of semi-structured interviews, involving questions about their continuing education, followed by transcription of the words to analysis and interpretation of collected information, emphasizing the content analysis. The results showed that there is a distinct difference between the two IES in relation to continuing education conception by participating teachers; As relative to support of the IES to the completion of training and the teachers working day, in that the public institution involved teaching, the research and the extension, while the private institution prioritizes the teaching. The common points were found relative to teachers expectations about what continuing education model should be developed and the little modification that the continuing education promoted the careers of these teachers considering the formation model experienced by them. So, investigations about this process are too important because they show the continuing education reality in the IES and seek the reflection and action front of the theme.